Perbuatan Melawan Hukum Terhadap Pembongkaran Bangunan Atas Objek Sewa Menyewa - Max Gilberth Emillio Veerman; Merry Tjoanda; Sarah Selfina Kuahaty (PATTIMURA Law Study Review, 2026)
Acts against the law can be interpreted in Article 1365 of the Civil Code stated that "every act against the law that brings loss to others, obligating people because of their wrongdoing to cause losses that, compensates for these losses.” In this case Cam Larenissa violated Article 1365 of the Civil Code because he had taken action which harms other people who have done damage or demolition of stalls belonging to the second party, namely Wa Tati, without his knowledge and without asking permission from party I as the land owner, namely Daniel Sohilait. The research method used is normative legal research. There are three problem approaches used, namely the statutory approach, the conceptual approach and the case approach. Source of legal materials used are primary, secondary and tertiary legal materials. The results of the research include: (1) Building demolition carried out by a third party is an action included in the act against the law based on the provisions and elements contained in civil law; (2) Building demolition is mandatory provide compensation to parties who have been harmed as a form of The unlawful act in this case is compensation that must be borne by third parties, namely material and immaterial.